2019
DOI: 10.30598/molmed.2019.v12.i2.1
|View full text |Cite
|
Sign up to set email alerts
|

HUBUNGAN AKTIVITAS FISIK DAN KUALITAS TIDUR DENGAN KADAR GULA DARAH SEWAKTU PADA PASIEN DIABETES MELITUS TIPE 2 DI POLIKLINIK PENYAKIT DALAM RSUD dr. M. HAULUSSY AMBON

Abstract: Pendahuluan. Diabetes melitus adalah suatu kelompok penyakit metabolik dengan karakteristik hiperglikemia yang terjadi karena gangguan sekresi insulin, kerja insulin, atau kedua-duanya. Aktivitas fisik dan kualitas tidur berperan sebagai pengendali kadar gula darah dan menurunkan resistensi insulin pada penderita diabetes melitus tipe 2. Tujuan. Penelitian ini bertujuan untuk mengetahui hubungan aktivitas fisik dan kualitas tidur dengan kadar gula darah sewaktu pada pasien diabetes melitus tipe 2. Metode. Pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The outcomes of this study are also underpinned by study done by [8], regarding the relationship between body movements and sleep quality with levels of blood sugar in patients with type 2 diabetes mellitus at the Internal Medicine Polyclinic, dr. M. Haulussy Ambon. The results showed that there was a significant relationship between body movements and levels of blood sugar, p = 0.002.…”
Section: The Relationship Between Body Movements and Levels Of Blood Sugarmentioning
confidence: 97%
See 2 more Smart Citations
“…The outcomes of this study are also underpinned by study done by [8], regarding the relationship between body movements and sleep quality with levels of blood sugar in patients with type 2 diabetes mellitus at the Internal Medicine Polyclinic, dr. M. Haulussy Ambon. The results showed that there was a significant relationship between body movements and levels of blood sugar, p = 0.002.…”
Section: The Relationship Between Body Movements and Levels Of Blood Sugarmentioning
confidence: 97%
“…Body movements is very important in the management of diabetes mellitus, especially as controlling blood sugar and developing cardiovascular hazard factors like reducing hyperinsulinemia, developing insulin responsiveness, cutting body fat, and lowering blood pressure. Routine body movements is integrated with a decrease in mortality by around 45-70% in the population of type 2 diabetes mellitus and lowering levels of blood sugar which can prevent complications [8].…”
Section: The Relationship Between Body Movements and Levels Of Blood Sugarmentioning
confidence: 99%
See 1 more Smart Citation
“…Menurut studi terdahulu, bahwa aktivitas fisik berhubungan signifikan terhadap kadar gula darah sewaktu yakni (p=0,002). 16 Namun, selain aktivitas fisik yang kurang, kebiasaan merokok juga berpengaruh terhadap terjadinya resistensi insulin. Temuan studi ini menunjukkan bahwa remaja yang memiliki kebiasaan merokok terdapat sebanyak 16,2%.…”
Section: Pembahasanunclassified
“…female category, namely 79.7%, the age of the respondents was more in the 21-25 year age category, 59.5%, ethnicity was more in the Batak category, namely 62.2%, abnormal body mass index is 30.4%, respondents who have a family history are 15.5%, lack of physical activity are 22.3%, and respondents who have smoking habits are 16.2%. Respondents who had less knowledge were 43.2% and those who had good knowledge were 56.8%.…”
mentioning
confidence: 99%